Inclusion of Orogastric Tube in the Staple Line During Laparoscopic Roux-en-Y Gastric Bypass: an Avoidable Complication - Jain, Sandeep; Baksi, Aditya; Kumar, Amardeep; Aggarwal, Sandeep (Obesity surgery, 2021)
Purpose Laparoscopic Roux-en-Y gastric bypass (LRYGB) involves creation of a small gastric pouch by sequential firing of stapler. During stapler firing, the orogastric tube (OGT) needs to be withdrawn to avoid inclusion in the staple line. We report a rare complication of inadvertent stapling of the OGT during creation of the gastric pouch. Materials and Methods A 37-year old man with body mass index (BMI) of 52.5 kg/m 2 and type 2 diabetes mellitus, obstructive sleep apnoea, and gastro-oesophageal reflux disease, underwent LRYGB, with a biliopancreatic limb of 70 cm and an alimentary limb of 130 cm. Before firing the stapler for gastric pouch, the anaesthesia team was requested to withdraw the OGT, and they confirmed that it was done. The stapler was fired without any difficulty. Gastrojejunostomy was also done using linear stapler without any hindrance. The enterotomies were closed with absorbable sutures. Methylene blue leak test was found to be negative. Just before extubation, the anaesthesia team asked us if the OGT could be removed! To our horror, the OGT could not be pulled out on gentle tugging, confirming inclusion of the OGT in the staple line. The patient was induced again and re-explored immediately, with endoscopic guidance. Both the pouch and remnant stomach were opened, the cut ends of OGT freed from both staple lines, and the tube removed. The openings in the pouch and remnant stomach were closed with stapler. Methylene blue leak test and air insufflation test were done and found to be negative. Results Postoperative recovery was uneventful and the patient was discharged on day 5. Review of the recorded video was done but the OGT was not visualised through the initial gastrotomy as the OGT had possibly been stapled during the last vertical firing higher up near the fundus. Discussion Stapler firing over the OGT can occur insidiously without the surgeon’s awareness. In this case, it was only suspected when the anaesthesia team asked us matter-of-factly whether the OGT could be removed. We had presumed that it had been removed before the first firing. Some surgeons prefer to keep the OGT for a day after surgery. Had that been our practice, this complication would have mandated a re-surgery in the early postoperative period. Such complications occur when the surgeon fails to request the anaesthesia team to remove the OGT or if there is poor communication between the surgical and anaesthesia teams. Sometimes, it can be due to change in the anaesthesia team during the procedure. In our case, though the anaesthesia team was the same, there was a new anaesthesia registrar who was involved in a bariatric surgical case for the first time. Use of transparent drapes, if available, may be advantageous, enabling the surgical team to see the OGT. The openings in the pouch and remnant stomach were closed with a stapler, as it was thought to be a more secure and faster method than oversewing. However, if the pouch is too small to allow stapler closure, simple suture closure should be done. Conclusion Inclusion of orogastric tube in the staple line should be a ‘never event’. This case report highlights the importance of good communication between the surgical and anaesthesia teams, not only during the staple fire, but throughout the procedure.